JAVANESE NATIVE RESISTANCE AGAINSTS COLONIAL’S AUTHORITY IN PRAMOEDYA ANANTA TOER’S “THIS EARTH OF MANKIND” - FITROKHI DANIEL AKBAR (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2015)
Abstract The aim of the study is to answer two question which are stated in the problem formulation, namely (1) To describe how Colonial’s authority suppression triggers the reaction of native Javanese’s resistance in Pramoedya Ananta Toer’s This Earth of Mankind and (2) To describe how is native Javanese’s resistance against Colonial’s authority in Pramoedya Ananta Toer’s This Earth of Mankind. The Javanese Native resistance and the Colonial suppression are the trigger of natives reaction. Pramoedya he is the greatest Indonesian-humanism who always concerns with the equality of human right. His concerns are reflected on almost all of pieces of writings and works which endow the message to make human becomes more sensitive to others need. The Javanese native’s resistance focuses on the two charatcters as the main characters and representations, they are Minke and Nyai Ontosoroh. The research is descriptive qualitative. Type of the data and the data source taken from two data source is primary and secondary. The primary data source is This earth of Mankind novel written by Pramoedya Ananta Toer released in 1975. The secondary data sources are taken from theory, other source and internet related to the study. The technique of collecting data is documentation. The steps are reading novel, classfying and analyzing the data, taking note and browsing to the internet. Based on the analysis, the study shows that the problem faced by the major character is the own psychology condition to decide the appropriate ways for his life. Their resistance against colonial’s authority is in the form of empowering themself in higher education. The result of this study is colonial’s power can be banned by the Javanese native almost in every aspect of life. Keywords: resistance, javanese, native, colonial, authority, suppression